A place to call home?: A qualitative exploration of public librarians' response to homelessness. Issue 4 (2nd October 2017) - Giesler, Mark A.
ABSTRACT: Labeled "third-sector" community organizations, public libraries serve homeless individuals by default. Using focus group interview data with library personnel, this qualitative study explored how public libraries in 8 urban and suburban communities in one Midwestern state perceived and served homeless patrons. Three themes emerged: (1) the recognition that libraries serve as makeshift shelters, (2) the inconsistent implementation of code of conduct policy regarding homeless patrons; and (3) innovative "under the radar" responses by administration and staff to resolve the tensions enacted by the presence of homeless persons in library facilities. Recommendations for staff training, internal policy revision, and enhanced collaboration between social service agency and public library staff are provided.